Behaviour of high-strength concrete circular columns confined by high-strength spirals under concentric compression - Hou, Chongchi; Zheng, Wenzhong; Chang, Wei (Journal of Civil Engineering and Management, 2020)
This paper tested the behaviour of 32 high-strength concrete columns confined by high-strength spirals under concentric compression. The test parameters included unconfined concrete compressive strength, spiral yield strength, volumetric ratio, and spiral spacing. The results showed that bulging and shear sliding were the two characteristic types of failure patterns of the thirty-two confined columns, depending on spiral spacing and concrete strength. Moreover, the spiral in most specimens did not yield at the confined concrete compressive strength. An analytical confinement model for high-strength concrete columns confined by high-strength spirals was proposed. In this proposed model, the calculated value of the spiral stress at the confined concrete compressive strength was used to calculate the feature points of the stressstrain curve. The proposed model showed good correlations with available experimental results of 64 columns.